Calorie Restriction With Exercise Intervention Improves Inflammatory Response in Overweight and Obese Adults: A Systematic Review and Meta-Analysis - Liu, Yubo; Hong, Feng; Lebaka, Veeranjaneya Reddy; Mohammed, Arifullah; Ji, Lei; Zhang, Yean; Korivi, Mallikarjuna (Frontiers in Physiology, 2021)
Background/Purpose: In this systematic review and meta-analysis, we assessed the effects of exercise (EX) combined with calorie restriction (CR) intervention on inflammatory biomarkers, and correlations between biomarkers and participants’ characteristics were calculated in overweight and obese adults. Methods: Article search was conducted through PubMed, Web of Science, EMBASE, Cochrane database, Scopus, and Google Scholar to identify the articles published until April 2021. Studies examined the effect of EX+CR intervention on inflammatory biomarkers, including C-reactive protein (CRP), interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α), and compared with CR trial in overweight and obese adults were included. We calculated the pooled effect by meta-analysis, identified the correlations (between inflammatory biomarkers and participants’ characteristics) through meta-regression, and explored the beneficial variable through subgroup analysis. Cochrane risk of bias tool and Methodological Index for Non-Randomized Studies were used to assess the risk of bias for the included trials. Results: A total of 23 trials, including 1196 overweight and obese adults, were included in the meta-analysis. The pooled effect showed that EX+CR intervention significantly decreased CRP levels (P=0.02), but had no effect on IL-6 (P=0.62) and TNF-α (P=0.11). Meta-regression analysis showed that the effect of EX+CR on CRP, IL-6 and TNF-α changes was correlated with lifestyle behavior of adults (Coef.=-0.380, P=0.018; Coef.=-0.359, P=0.031; Coef.=-0.424, P=0.041, respectively), but not with age and BMI. The subgroup analysis results revealed that participants with sedentary lifestyle behavior were not responded to EX+CR intervention, as we found no changes in CRP, IL-6 and TNF-α concentrations (P=0.84, P=0.16, P=0.92, respectively). However, EX+CR intervention significantly decreased CRP (P=0.0003; SMD=-0.39; 95%CI:-0.60 to -0.18), IL-6 (P=0.04; SMD=-0.21; 95%CI:-0.40 to -0.01) and TNF-α (P=0.006; SMD=-0.40, 95%CI: -0.68 to -0.12) in adults without sedentary lifestyle or normal lifestyle. Furthermore, the values between sedentary and normal lifestyle subgroups were statistically significant for CRP, IL-6 and TNF-α. Conclusions:Our findings showed that combination EX+CR intervention effectively decreased CRP, IL-6 and TNF-α in overweight and obese adults with active lifestyle, but not with sedentary lifestyle behavior. We suggest that ‘lifestyle behavior’ is a considerable factor when designing new intervention programs for overweight or obese adults to improve their inflammatory response.